ARLITAR: augmented reality for basic circuit learning module / Noor Azah Samsudin ... [et al.] - Samsudin, Noor Azah; Rosman, Anatun Nadrah; Aripin, Muhammad Syariff; Ahmad Khalid, Shamsul Kamal (Universiti Teknologi MARA, Kedah, 2019)
This project focus on delivering an application of essential components on basic electric circuit topic using augmented reality approach. The content of the electric circuit topic application is implemented to guide students to learn basic concept of electric circuit with some demonstrations and exercises. The content is presented on a mobile application platform, namely, ARLITAR. The augmented reality approach has applied simulation of two dimensional (2D) and three dimensional (3D) objects. The presentation of the ARLITAR is a practical approach to encourage interactive learning activities which eventually enhance students’ understanding towards important elements in electric circuit. Thus, the ARLITAR application is also equipped with a module that can be released for reference to potential users among students and teachers.